EFEKTIVITAS METODE TAMRINUL MUSABAQOH TILAWATIL KITAB (TMTK) DALAM MENINGKATKAN KEMAMPUAN BELAJAR MEMBACA KITAB KUNING DI MADRASAH ALIYAH DINIYAH PUTRA PONDOK PESANTREN MIFTAHUL ULUM BETTET PAMEKASAN - Muafi Muafi; Supandi Supandi; Syafrawi Syafrawi (Fakultas Agama Islam Universitas Islam Madura, 2023)
The background of this research is the decline in the ability to read and understand the Yellow Book of students, because it is the main foundation in understanding Islamic Religion. This is the main attraction for researchers in conducting research on this theme. The method used is a qualitative approach using a qualitative type of case study research using a phenomenological perspective. The results of this study are based on the research results obtained by researchers both through observation, interviews, and documentation that the implementation of the Tamrinul Musabaqoh Tilawatil Kitab Program held by Madrasah Aliyah Diniyah Putra Pondok Pesantren Miftahul Ulum Bettet Pamekasan can be seen and proven from the results of interviews with the head of the madrasa, teachers and students themselves. This indicates the acceptance of the title of this thesis so that it is not rejected. The implication of this research is that this research provides experience and an overview for pesantren managers and santri to restore the characteristics of santri and pesantren who are good at understanding and reading the yellow book which is the hallmark of pesantren graduates. Then because the yellow book is a typical reference in the implementation of learning in pesantren in the enrichment of science, especially in the study of religious sciences and so on.